Metals in coastal mollusks of Costa Rica - Vargas Zamora, José A. (2015)
The input of contaminants to coastal ecosystems is a global problem on the rise. Data on metal pollution from tropical sites is often lacking and pilot surveys are urgently needed to provide a general framework to estimate the relative impact of these and other pollutants. The objective of this study was to make accessible data on trace metals collected during pilot surveys (2000-2006) at four coastal embayments of Costa Rica. Concentrations of Fe, Pb, Zn, Mn, and Ni were determined by Flame Atomic Absorption Spectrometry (FAAS) and Graphite Furnace Atomic Absorption Spectrometry (GFAAS), in tissues of the rock snail Acanthais brevidentata, the infaunal bivalves Anadara tuberculosa and Tagelus affinis from three Pacific shorelines (Culebra Bay, Gulf of Nicoya, and Golfito Bay) and in the clam Polymesoda arctata from the Caribbean coast (Moín Bay). In addition, Sn, Cd and Cu were evaluated in tissues of T. affinis. A group of specimens of T. affinis was depurated for 72 hours in filtered seawater from the collection site. Concentrations varied between and within sites and also between parts of the same organisms. Maximum concentrations (μg/g dry weight) were: Fe 2 230 (P. arctata-tissues, Moín Bay), Pb 195 (P. arctata-tissues, Moín Bay), Zn 961 (A. brevidentata-tissues, Golfito Bay), Mn 921(P. arctata-tissues, Moín Bay), and Ni 10.5 (A. tuberculosa-shells, Golfito Bay). Minimum concentrations (μg/g dry weight) were: Fe 5.36 (P. arctata-tissues, Moín Bay), Pb < 0.20 (P. arctata-foot, Moín Bay), Zn 2.75 (P. arctata-shell, Moín Bay), Mn 5.5(A. tuberculosa-foot, Gulf of Nicoya) and Ni 0.83 (A. tuberculosa-foot, Golfito Bay). Tissues of non-depurated T. affinis had maximum-minimum concentrations (μg/g dry weight) of Sn (3.74-2.73), Cd (0.69-0.43) and Cu (21.6-14.8). The concentrations (except for Pb and Mn) were within values reported in recent literature. The relatively high concentration of Pb was probably related to the use during sampling of leaded fuel in small boat operation at the site, while no evident cause was found for the high Mn values. Depuration was partially effective in lowering the metal burden in T. affinis. Data gathered during the pilot survey are indicative of relatively clean conditions of Culebra Bay, while the other three sites have important concentrations of certain contaminants, including metals. In spite of the fact that this data was collected more than a decade ago, it remains as the most recent available on trace metals from coastal mollusks of Costa Rica.